تحديات التعليم الإلكتروني في ظل تطبيق الإدارة الإلكترونية - نبيح، أمينة; غراز، الطاهر (مركز فكر للدراسات والتطوير, 2022)
أنتجت تقنية المعلومات والاتصالات وتطبيقاتها المتطورة والمتجددة، واقعا إداريا جديدا، تجلت مظاهره في سقوط كثير من المفاهيم الفكرية والمنظومات التي اعتمدت عليها الدراسات الإدارية سابقا، حيث جعلت الأساليب الإدارية الحديثة تكاد لا تمت بصلة لما كان عليه واقع الفكر الإداري وتطبيقاته خلال العقد الماضي. وبفعل ذلك فقد تأثرت المنظمات المعاصرة، ومنها المؤسسات التعليمية وتغيرت هياكلها ومعاملاتها ومعايير أدائها، وامتد نطاق خدماتها إلى خارج المواقيت الرسمية، سعيا لإنجاز تعاملاتها متعدية حدود الزمان والمكان، وصولا إلى خدمات تتسم بالسرعة والشفافية والنزاهة. وتأسيسا على ما سبق نسعى من خلال هذا المقال إلى تسليط الضوء على مفهوم الإدارة الإلكترونية وتطبيقاتها في مجال التعليم، مع إبراز أهم العوائق التي تحد من تطبيقها. Over the past few years, information and communication technologies (ICT) and their advanced applications have produced a new administrative reality, manifested in the fall of many intellectual concepts and systems upon which administrative studies relied upon, where modern administrative methods have become almost irrelevant to the reality of administrative thought and its applications during the past few years last decade. In doing so, contemporary organizations, including educational institutions, have been affected and their structures, transactions and performance standards have changed, and their services have extended beyond official times, in pursuit of their transnational and time-bound transactions, leading to speedy, transparent and impartial services. Based on the above, we seek through this article to highlight the concept of e-management and its applications in the field of education, highlighting the most important obstacles that limit its application.
Keywords: الأنظمة الإلكترونية الإدارية -- التعليم الإلكتروني -- المؤسسات التعليمية -- الإدارة المدرسية